A formula for the sum of $n$ weak$^\star $ closed sets in $L^∞ $ - Zivari-Rezapour, Mohsen; Liu, Yichen; Emamizadeh, Behrouz (Comptes Rendus. Mathématique)
In this note, we derive an equation which describes the closure of a particular set comprising $n-$valued functions. This result provides an answer to a long standing question for which the particular case $n=2$ had been known and used frequently in the optimal control problems.